A New Antimicrobial Phenylpropanol from the Leaves of Tabernaemontana inconspicua Stapf. (Apocynaceae) Inhibits Pathogenic Gram-Negative Bacteria - Lidwine Ngah; Willifred Dongmo Tékapi Tsopgni; Judith Caroline Ngo Nyobe; Alain Tadjong Tcho; Moses K. Langat; Jean Claude Ndom; Eduard Mas-Claret; Nicholas John Sadgrove; Alain François Kamdem Waffo; Methee Phumthum (MDPI AG, 2022)
A chemical investigation of the leaves of Tabernaemontana inconspicua Stapf. led to the isolation of a new phenylpropanol derivative, namely irisdichototin G (1), together with nine known compounds, including one polyol derivative, dambonitol (2); three alkaloids, 10-hydroxycoronaridine (3), voacristine (4) and vobasine (5); two triterpenes lupeol (6), betulinic acid (7) and three sterols, sitosterol (8), sitosterol-3-O-β-D-glucopyranoside (9) and stigmasterol (10). The structure of the new compound, as well as those of the known ones, was established by means of spectroscopic methods: NMR analysis (1H and 13C NMR, 1H-1H-COSY, HSQC, HMBC and NOESY), high-resolution mass spectrometry (HR-ESI-MS) and comparisons with previously reported data. Among the known compounds, compound 2 was firstly reported from the family Apocynaceae. Compounds 1-5 were tested for their antimicrobial effects against three Gram-negative organisms associated with human wound and systemic infections, namely Haemophilus influenzae 9435337A, Klebsiella pneumoniae 17102005 and Pseudomonas aeruginosa 2137659B. Compounds 1, 3, and 5 showed significant antimicrobial effects with minimum inhibitory concentrations (MIC) of 62.5 μg/mL, 62.5 μg/mL and 7.81 μg/mL, respectively, against Haemophilus influenzae, whereas compounds 1 and 5 showed significant antimicrobial effects, with a MIC value of 31.25 μg/mL against Pseudomonas aeruginosa. In addition, compound 3 showed significant antimicrobial activity, with a MIC value of 31.25 μg/mL against Klebsiella pneumoniae.